2017
DOI: 10.3390/nu9050496
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Protective Effects of Dried Plum in Postmenopausal Women: Efficacy and Possible Mechanisms

Abstract: Osteoporosis is an age-related chronic disease characterized by a loss of bone mass and quality, and is associated with an increased risk of fragility fractures. Postmenopausal women are at the greatest risk of developing osteoporosis due to the cessation in ovarian hormone production, which causes accelerated bone loss. As the demographic shifts to a more aged population, a growing number of postmenopausal women will be afflicted with osteoporosis. Certain lifestyle factors, including nutrition and exercise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…104 Although bioactive compounds in isolation can have wide-reaching health benefits through antioxidant and anti-inflammatory actions, they are known to act additively and synergistically to elicit a more pronounced biological effect when consumed together. 105,106 A recent study demonstrated that grape seed phenolic extract that contains many phytochemicals positively influenced bone healing by increasing the mechanical strength of the healing femur. 107 Though these compounds show some promise in pre-clinical animal studies, several important questions remain (Fig.…”
Section: Emerging Areas and Future Perspectives Nontraditional Dietarmentioning
confidence: 99%
“…104 Although bioactive compounds in isolation can have wide-reaching health benefits through antioxidant and anti-inflammatory actions, they are known to act additively and synergistically to elicit a more pronounced biological effect when consumed together. 105,106 A recent study demonstrated that grape seed phenolic extract that contains many phytochemicals positively influenced bone healing by increasing the mechanical strength of the healing femur. 107 Though these compounds show some promise in pre-clinical animal studies, several important questions remain (Fig.…”
Section: Emerging Areas and Future Perspectives Nontraditional Dietarmentioning
confidence: 99%
“…Dried plum, Prunus domestica L., has been shown to have beneficial effects against bone loss 31 (reviewed in Wallace et al 2017). Dried plum's positive effects on bone health markers have been investigated in multiple models of osteopenia, in both human clinical trials [32][33][34][35][36] and rodent studies 37,38 . While the mechanism of action of dried plum is still unknown, it has been hypothesized that the high antioxidant capacity and high polyphenolic content of this fruit scavenges free-radicals as well as promotes bone formation and inhibits bone resorption [39][40][41][42] .…”
mentioning
confidence: 99%
“…In rat models of osteoporosis, dried plum intake resulted in prevention and reversal of bone loss [43,44]. A three-month clinical intervention study showed that dried plum intake improved biomarkers of bone formation in postmenopausal women, whereas longer term intake of dried plum resulted in mitigating loss of bone mineral density [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plums have been extensively studied for their effects on bone health [29,30]. Plums contain caffeic acid (the polyphenol component of neochlorogenic and chlorogenic acids) and rutin, which have been shown to inhibit the deterioration of bone tissues and prevent diseases such as osteoporosis in postmenopausal women [31].…”
Section: Introductionmentioning
confidence: 99%